Cardiac pulse detection by a pulse train using the synchronous demodulation technique: Detección del pulso cardíaco mediante un tren de pulsos utilizando la técnica de demodulación síncrona - Yañez Mendiola, Javier; Bautista López, Roxana Zaricell; López Vela, José Martin (LATAM Revista Latinoamericana de Ciencias Sociales y Humanidades, 2025)
Photoplethysmography is a widely studied noninvasive optical technique with great potential for application in clinical medicine. There is evidence that the PPG signal can provide information about heart rate, oxygen saturation in arterial blood, respiratory rate among other cardiovascular signs. The two-wavelength photoplethysmographic signal is generally used to determine oxygen saturation in arterial blood under the principle that oxygenated and deoxygenated hemoglobin differentially absorb red and near-infrared wavelengths. In this work it is proposed to use the same wavelengths that are used in the pulse oximetry technique (660 nm and 940 nm) to calculate heart rate; Heart rate recovery is done by analyzing the data using the synchronous demodulation technique. The sampled data was generated from measurement carried out on two people. The heart rate obtained with the pulse oximetry technique in conjunction with the synchronous demodulation technique was corroborated with the heart rate obtained using the PPG signal at a single wavelength (940 nm).